Recenzja książki Łukasza M. Nadolskiego i Arkadiusza Kalińskiego pt. Bydgoszcz 1945, Bydgoszcz 2011, s. 128, wyd. II (Kronika Bydgoska, 2010)
The Polish literaturę published so far about the liberation of Bydgoszcz from the German occupation disregarded this problem, writing about a relatively quick and smooth seizure of the city by the Red Army and the Polish Army. The reviewed work based on numerous sources shows a different picture of the events. On January 24-27, 1945, fierce fights waged in the streets of the city took heavy casualties.